2019
DOI: 10.1590/1413-81232018241.35422016
|View full text |Cite
|
Sign up to set email alerts
|

Survival rates of breast cancer and predictive factors: a hospital-based study from western Amazon area in Brazil

Abstract: Survival rates of breast cancer and predictive factors: a hospital-based study from western Amazon area in BrazilSobrevida do câncer de mama e fatores preditivos: um estudo de base hospitalar do oeste amazônico, Brasil Resumo Na América Latina, a sobrevida de 5 anos do câncer de mama está abaixo dos países da Europa central. Não há estudos de sobrevida de câncer de mama de base hospitalar no oeste da Amazônia brasileira. O objetivo deste artigo é estimar a sobrevida hospitalar de câncer de mama e fatores assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 26 publications
4
9
0
Order By: Relevance
“…In agreement with what was previously reported in Jordan, 27 Brazil, 45 and Iran 24 patients who were surgically treated showed better survival than those treated with combined therapy of surgery, radiotherapy, and chemotherapy but without significant difference. Contrarily to that reported in Oman, 42 chemotherapy alone was associated with a worse prognosis.…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with what was previously reported in Jordan, 27 Brazil, 45 and Iran 24 patients who were surgically treated showed better survival than those treated with combined therapy of surgery, radiotherapy, and chemotherapy but without significant difference. Contrarily to that reported in Oman, 42 chemotherapy alone was associated with a worse prognosis.…”
Section: Discussionsupporting
confidence: 92%
“…These survivals are close to those observed in other national studies [10,19,20] and lower than those found in countries like U.S.A. and England [5,9].…”
Section: Discussionsupporting
confidence: 88%
“…However, very young women (those under 40 years old) had a 5yOS of 82.2%, signi cantly less than women aged 40 to 49, 87.7% (p = 0.002). Other studies also point to reduced survival in very young women [7,8,20], probably due to the diagnosis of more aggressive molecular types of tumours found in this group.…”
Section: Discussionmentioning
confidence: 91%
“…In this study, we demonstrated 5-year OS rate of 58%, a little higher than that reported in Uganda (51.8%), Ghana (47.9%), Indonesia (51.1%), and Malaysia (49%), 32 35 and less than that reported from Eastern Mediterranean region (69.2%), India (78%), Vietnam (80.6%), and Brazil (87%). 36 39 Yet, this rate was much lower than survival rates in more developed countries such as the United States (91%), Canada (88%), Australia (88.3%), Japan (85.5%), and Western European countries—which generally exceed the limit of 85%. 14 , 16 , 40 The low OS rate observed in African women could be because of late presentation and aggressive nature of BC, together with lack of screening programs and limited access to healthcare services.…”
Section: Discussionmentioning
confidence: 87%